Inhibition effect of potassium iodide on the corrosion of carbon steel (XC 38) in acidic medium - Attar, Tarik; Larabi, Lahcène; Harek, Yahia (International Journal of Advanced Chemistry, 2014)
The effect of potassium iodide (KI) on the corrosion of carbon steel (XC38) in 0.5 M H2SO4 has been investigated in relation to the con-centration of the inhibitor by weight loss measurement. It was found that the inhibition efficiency increases with an increase in concentration of inhibitors and temperature. The effect of temperature on the corrosion behavior with the addition of optimal concentration of KI was studied in the temperature range 293-323 K. The adsorption of the inhibitor on the XC38 surface is in agreement with Temkin adsorption isotherm. On the bases of thermodynamic adsorption parameters, it can be interpreted that the adsorption of this inhibitor on the carbon steel surface takes place through both chemical and physical adsorption. Keywords: Corrosion Inhibition, Weight Loss, Carbon Steel, Adsorption Isotherm, Thermodynamic Parameters.